Efektivitas Aplikasi Program e-Kinerja Berbasis e-Government (Studi Kasus pada Bagian Sumber Daya (BAGSUMDA) Polresta Sidoarjo) - Anggia Kartika Sari; Sri Umiyati; M. Husni Tamrin; Susi Ratnawati (FISIP UWP, 2023)
This study aims to analyze the Effectiveness of the E-Government-Based E-Performance Program Application in the Resources Section of the Sidoarjo Police. This study uses a descriptive qualitative method with a case study approach. The existence of the E-Kinerja application can increase work transparency and personnel welfare by getting benefits according to performance results. The data sources used are secondary data and primary data obtained through interviews, observations and documentation. There are six variables to measure program effectiveness, namely 1) Program Understanding 2) Right on Target 3) On Time 4) Achievement of Goals 5) Real Change 6) Availability of Facilities and Infrastructure. The research results show that the Effectiveness of the E-Performance Program Application in the Resources Section (Bagsumda) of the Sidoarjo Police is said to be Effective, there are seven sub-indicators that are already running well, namely Performance Achievement, Program Realization to be achieved by an institution, Performance Transparency, Improvement Performance, Work Achievement, Employee Welfare, and Applications. However, there are indicators that have not gone well, namely, the time used to fill out the E-Kinerja, there are still personnel who are late filling out the Work Diary and the available Internet is still slow